2012
DOI: 10.1007/s10933-012-9611-8
|View full text |Cite
|
Sign up to set email alerts
|

1750 years of large rainfall events inferred from particle size at East Lake, Cape Bounty, Melville Island, Canada

Abstract: Annual grain-size variation was measured on the varved (annually laminated) lacustrine sediment from Cape Bounty East Lake using an innovative image analysis system. About 7100 images were acquired using a scanning electron microscope and processed to obtain measurement of particles from 2845 varves. Several particle-size distributions indices were calculated and can be linked to high-energy sedimentary facies. Moreover, the coarse grain size (98th percentile) of these high-energy facies is strongly correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 38 publications
4
63
0
Order By: Relevance
“…For example, Lapointe et al . [] documented a recent increase in coarse particles being deposited in East Lake, which they linked to an increase in summer rainfall intensity since 1920. This increase in rainfall is suggested to be a response to the ongoing warming of the Arctic.…”
Section: Regional Settingsmentioning
confidence: 99%
“…For example, Lapointe et al . [] documented a recent increase in coarse particles being deposited in East Lake, which they linked to an increase in summer rainfall intensity since 1920. This increase in rainfall is suggested to be a response to the ongoing warming of the Arctic.…”
Section: Regional Settingsmentioning
confidence: 99%
“…Many studies suggested that the amount and grain size of eroded, transported and deposited material in case of flood events are controlled by the river discharge (e.g. Schiefer et al, 2011;Lapointe et al, 2012;Jenny et al, 2014;Wilhelm et al, 2015). Therefore, flood processes seem to be the best candidate to trigger GB-I.…”
Section: Trigger Of Gb-i and Gb-iimentioning
confidence: 99%
“…The magnitude of past flood events may be reconstructed through grain size (e.g. Schiefer et al, 2011;Lapointe et al, 2012;Wilhelm et al, 2015;Schillereff et al, 2014) or through the total volume of sediments transported and deposited during the flood (e.g. Jenny et al, 2014;Wilhelm et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The papers in this Special Issue explore a large variety of paleoenvironmental indicators, including some emerging techniques, such as analyzing the isotopic composition of specific compounds (Thomas et al 2012;Wooller et al 2012a), measuring particle-size distribution from thin-section imagery (Lapointe et al 2012), and fusing data from different proxy types (Helama et al 2012). Many studies are notable for their multi-proxy approach.…”
Section: Proxy Typesmentioning
confidence: 99%
“…Lapointe et al (2012) used the correlation between annual particle-size distribution and rainfall during the instrumental period to reconstruct summer rain events during the past 1,750 years at East Lake in the Canadian High Arctic. Thomas et al (2012) found a relationship between varve thickness and d 2 H values of leaf waxes in sediment from glacier-fed Ayr Lake on Baffin Island; on centennial time scales, low d 2 H values and thin varves are associated with the coldest decades of the last two millennia.…”
Section: Late Holocene Recordsmentioning
confidence: 99%